BIOFABRICATION OF AN OVINE INTERVERTEBRAL DISC MODEL BY COMBINING A POLYCAPROLACTONE FRAME WITH A BIOPRINTED ALGINATE HYDROGEL - Monaghan, Michael (My University, 2025)
The intervertebral disc (IVD) primarily comprises an outer ring of collagen fibers (annulus fibrosus, AF), which encases a soft, gelatinous core (nucleus pulposus, NP). Existing in vitro models have failed to integrate these two tissues effectively or accurately replicate their intricate organization. By combining two biofabrication techniques, we developed a novel 3D in vitro model that closely mimics the organization of an ovine IVD. Our approach employs a polycaprolactone (PCL) frame produced via melt electrowriting to recreate the multilamellar architecture of the annulus fibrosus. Ovine primary cells, encapsulated in a photocrosslinkable alginate hydrogel, were precisely extruded within the multilamellar structure, thereby mimicking the native shape and size of an ovine disc. The bioink containing the NP cells was deposited at the center of the construct, while the bioink with the AF cells was strategically layered in between the lamellae of the PCL frame. Photocrosslinking was optimized to match the native stiffness of the disc. The constructs were maintained in culture for 28 days, during which we thoroughly assessed reproducibility, stability, and cell viability and phenotype. The results unequivocally demonstrated that the PCL frame effectively guided the alignment and proliferation of AF cells, while the alginate hydrogel preserved NP cell phenotype. This model successfully replicates the organization of the IVD, providing a promising platform for advancing our understanding of disc biology and driving the development of novel therapeutic strategies.
PUBLISHED
Keywords: Extrusion-based bioprinting; 3D printing; in vitro model; Melt electrowriting; Spine; Nanoscience & Materials; Bioengineering